Mixed Chimerism and Secondary Engraftment Failure in Allogeneic Transplantation for Aplastic Anemia - Kako, Shinichi; Yamazaki, Hirohito; Ohashi, Kazuteru; Ozawa, Yukiyasu; Ota, Shuichi; Kanda, Yoshinobu; Maeda, Tetsuo; Kato, Jun; Ishiyama, Ken; Matsuoka, Ken-Ichi; Miyamoto, Toshihiro; Fukuda, Takahiro; et al. (Blood, 2018)
[Background] Mixed chimerism (MC) and/or secondary graft failure (SGF) with recipient or donor-type chimerism is a major obstacle in allogeneic hematopoietic stem cell transplantation for patients with aplastic anemia (AA). Recently, various kinds of conditioning regimen and donor are used in transplantation for AA, and their influences on MC and SGF remain to be elucidated. [Methods] In the Transplant Registry Unified Management Program (TRUMP), which is the registry database of the Japanese Society for Hematopoietic Cell Transplantation, patients with AA aged more than 15 years, who underwent a first allogeneic bone marrow or peripheral blood transplantation between 2000 and 2014 and achieved engraftment were eligible subjects of this study. A survey was conducted to collect the additional data regarding MC and SGF in each patient. [Results] Additional data were collected in 418 patients, and their median age was 30 years (range 16 - 65 years). A median follow-up period for survivors was 1727 days in all patients. MC requiring neither granulocyte-colony stimulating factor (G-CSF) nor transfusion support (Group 1), MC (not SGF) requiring G-CSF or transfusion support (Group 2), SGF with MC or complete recipient-type chimerism (Group 3), and SGF with complete donor-type chimerism (Group 4) developed in 26 (6.2 %), 16 (3.8 %), 19 (4.5 %), 17 (4.1 %) patients, respectively. Overall survival rates (OS) were 90.4 % at 1 year and 83.5 % at 5 years in patients without MC and SGF (Group 0, n = 340), which was not different from those in Group 1 (1yOS: 100.0 %, 5yOS: 94.1 %, P = 1.0) or Group 2 (1yOS: 87.5 %, 5yOS: 60.9 %, P = 1.0). In contrast, OS rates were significantly lower in Group 3 (1yOS: 52.1 %, 5yOS: 52.1 %, P < 0.001) and Group 4 (1yOS: 82.4 %, 5yOS 56.3 %, P = 0.003) as compared to Group 0 (Figure 1). SGF developed later in Group 4 than Group 3 (median days from transplantation: 99 days vs. 55 days, P = 0.04). In multivariate analyses, the use of fludarabine (Flu) (odds ratio: 4.26, P = 0.03) and no use of irradiation (odds ratio: 5.88, P < 0.001) in conditioning regimens were associated with the development of SGF with MC or complete recipient-type chimerism, and the use of Flu in conditioning regimens (odds ratio: 8.68, P = 0.04) was associated with SGF with complete donor-type chimerism. The dose of cyclophosphamide (CY), use of in vivo T-cell depletion in conditioning regimens, prophylaxis of graft-versus-host disease (GVHD), donor type, and stem cell source did not affect the development of SGF with both MC/recipient-type and donor-type chimerism. We further investigated the clinical course of patients with SGF, including the usage of post-transplant immunosuppressants (IS). SGF developed before starting the tapering of IS in 14 out of 19 patients in Group 3, and in 9 out of 17 patients in Group 4 (P = 0.299). After the onset of SGF, increase of IS was effective for SGF in only one patient in Group 3, but on the other hand, in 5 patients in Group 4. Decrease/discontinuation of IS was effective in one patient in Group 3, but none in Group 4. Second transplantation was successfully performed in 11 and 6 patients in Group 3 and 4, respectively. [Conclusion] The occurrence of SGF with both MC/recipient-type and donor-type chimerism after allogeneic transplantation for AA was associated with inferior OS, and conditioning regimens had an impact on the occurrence of SGF. The use of Flu may increase the occurrence of SGF with both MC/recipient-type and donor-type chimerism. When SGF occurs, efficacious intervention may differ according to the type of SGF. Kako:Takeda Pharmaceutical Company Limited.: Honoraria; Takeda Pharmaceutical Company Limited.: Honoraria; Celgene K.K.: Honoraria; Bristol-Myers Squibb: Honoraria; Sumitomo Dainippon Pharma Co., Ltd.: Honoraria; Chugai Pharmaceutical Co., Ltd.: Honoraria; Otsuka Pharmaceutical Co., Ltd.: Honoraria; Ono Pharmaceutical Co., Ltd.: Honoraria; Janssen Pharmaceutical K.K.: Honoraria. Kanda:Novartis: Research Funding; Sanofi: Research Funding; Tanabe-Mitsubishi: Research Funding; CSL Behring: Research Funding; Chugai: Consultancy, Honoraria, Research Funding; Taiho: Research Funding; Astellas: Consultancy, Honoraria, Research Funding; Taisho-Toyama: Research Funding; Otsuka: Research Funding; Takeda: Consultancy, Honoraria, Research Funding; Shionogi: Consultancy, Honoraria, Research Funding; Pfizer: Research Funding; Kyowa-Hakko Kirin: Consultancy, Honoraria, Research Funding; Nippon-Shinyaku: Research Funding; MSD: Research Funding; Asahi-Kasei: Research Funding; Ono: Consultancy, Honoraria, Research Funding; Eisai: Consultancy, Honoraria, Research Funding; Dainippon-Sumitomo: Consultancy, Honoraria, Research Funding; Bristol-Myers Squibb: Consultancy, Honoraria; Celgene: Consultancy, Honoraria; Mochida: Consultancy, Honoraria; Alexion: Consultancy, Honoraria; Takara-bio: Consultancy, Honoraria. Ishiyama:Alexion Pharmaceuticals, Inc.: Honoraria. Ichinohe:Zenyaku Kogyo Co.: Research Funding; Alexion Pharmaceuticals: Honoraria; Takeda Pharmaceutical Co.: Research Funding; Sumitomo Dainippon Pharma Co.: Research Funding; Taiho Pharmaceutical Co.: Research Funding; Ono Pharmaceutical Co.: Research Funding; Novartis.: Honoraria; Mundipharma: Honoraria; Janssen Pharmaceutical K.K.: Honoraria; JCR Pharmaceuticals: Honoraria; Otsuka Pharmaceutical Co.: Research Funding; Nippon Shinyaku Co.: Research Funding; MSD: Research Funding; Eisai Co.: Research Funding; CSL Behring: Research Funding; Kyowa Hakko Kirin Co.: Research Funding; Pfizer: Research Funding; Repertoire Genesis Inc.: Research Funding; Bristol-Myers Squibb: Honoraria; Celgene: Honoraria; Chugai Pharmaceutical Co.: Research Funding; Astellas Pharma: Research Funding. Mori:SHIONOGI: Honoraria; Janssen: Honoraria; Pfizer: Honoraria; Celgene: Honoraria; Taisho Toyama Pharmaceutical Co: Honoraria; Asahi Kasei: Research Funding; Astella Pharma: Honoraria; Shire Japan: Honoraria; Ono: Honoraria; MSD: Honoraria; Novartis Pharma: Research Funding; MSD: Research Funding; Novartis Pharma: Honoraria; CHUGAI: Honoraria; Japan Blood Products Organization: Honoraria; Kyowa Hakko Kirin: Honoraria; Eisai: Honoraria.